Audit of the Basic Education Data Application Information System (Dapodik) Juhut 1 State Primary School - Aryono, Gagah Dwiki Putra; Auliana, Sigit; Permana, Basuki Rakhim Setya; Arief, Rahadian; Azis, Marisa (ARRUS Journal of Engineering and Technology, 2024)
Basic Education Data Application (Dapodik) is an integrated national scale data collection system, and is the main national data source, which is part of the National Education planning program in creating intelligent and competitive Indonesian people. This research aims to find out how the information system created by the Department of National Education is right on target and easy to access. The object of this research is the Dapodik Application at SDN Juhut 1 Pandeglang Regency, the sample used in this research is the School Operator as the system user. Based on the survey results, the problems that occurred were still incomplete in the application and network menus at the school. So this problem can result in delays in the input process in the application used by the operator. The implementation of the Dapodik Application Information System at SDN Juhut 1 has followed the stages in the Dapodik Application guidebook.